Modulation of inflammasome activity by Porphyromonas gingivalis in periodontitis and associated systemic diseases - Ingar Olsen; Özlem Yilmaz (Journal of Oral Microbiology, 2016)
Inflammasomes are large multiprotein complexes localized in the cytoplasm of the cell. They are responsible for the maturation of pro-inflammatory cytokines such as interleukin-1β (IL-1β) and IL-18 as well as for the activation of inflammatory cell death, the so-called pyroptosis. Inflammasomes assemble in response to cellular infection, cellular stress, or tissue damage; promote inflammatory responses and are of great importance in regulating the innate immune system in chronic inflammatory diseases such as periodontitis and several chronic systemic diseases. In addition to sensing cellular integrity, inflammasomes are involved in the homeostatic mutualism between the indigenous microbiota and the host. There are several types of inflammasomes of which NLRP3 is best characterized in microbial pathogenesis. Many opportunistic bacteria try to evade the innate immune system in order to survive in the host cells. One of these is the periodontopathogen Porphyromonas gingivalis which has been shown to have several mechanisms of modulating innate immunity by limiting the activation of the NLRP3 inflammasome. Among them, ATP-/P2X7- signaling is recently associated not only with periodontitis but also with development of several systemic diseases. The present paper reviews multiple mechanisms through which P. gingivalis can modify innate immunity by affecting inflammasome activity.